MICROWAVE-ASSISTED SYNTHESIS OF N-(1H-IMIDAZOLINE-2-YL)-1H-BENZIMIDAZOL-2-AMINE AND ITS N-FUNCTIONALIZED DERIVATIVES - Servi, Suleyman; Genc, Murat (Taylor & Francis Inc, 2012)
N-(1H-Imidazoline-2-yl)-1H-benzimidazol-2-amine hydroiodide was synthesized with excellent yields, and it was converted to free base by using triethylamine under microwave irradiation (MWI) conditions. Its new Mannich, benzyl, and allyl derivatives were synthesized.
Keywords: 2-Aminobenzimidazole; guanidine; Mannich base; microwave irradiation